Characterization of patients with skin cancer and other affections caused by photodamage - Orquídea Isabel Alomá Magariños; Katiuska Tamayo Mariño; Josefa Eugenia Ruz Dominguez (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: Photodamage is the aggression caused by solar radiation in the skin. In turn, the ultraviolet radiation is one of the first agents considered as cancer generators.  Objective: Characterize the patients with cutaneous neoplasms and other affections caused by photodamage, according to selected clinical variables.  Methods: A cross-sectional, observational, clinical, descriptive and retrospective study of 64 patients diagnosed with some affection caused by photodamage was carried out, belonging to the health area of the doctor office No. 11 of Achiles Espinosa Salgado Polyclinic in Las Tunas, from January, 2020 to the same period in 2022. Some variables were analyzed, such as age, sex, color of the skin, skin photo type, occupation, regular use of solar protection means before the 18 years and now, as well as dermatologic disease caused by photodamage.  Results: There was a prevalence of the 60 years and over age group (43.7 %), female sex (54.7 %), color of the skin white (98.5 %), skin photo type III (59.4 %) and the state workers (53.1 %). It was found that 90.6 % of the patients didn't have history of exhibition to non ultraviolet radiations; 25.0 % referred to use some means of protection regularly before the 18 years and 51.5 % use it at the moment. The dermatologic disease caused by photodamage that prevailed was the skin cancer (37.5 %).  Conclusions: This study denoted the relevance and necessity to identify the clinical characteristics of the patients with affections caused by photodamage in the doctor office abovementioned.